Star wars art : visions - Lucas, George, 1944-; Rinzler, J. W. (Abrams, 2010)
George Lucas invited more than 100 well-known and promising artists to draw upon the entire Star Wars galaxy for inspiration. Star Wars: Visions collects these magnificent artworks for the first time. Features pieces by renowned artists such as Amano, Allan R. Banks, Harley Brown, Gary Carter, James Christensen, Michael Coleman, Kinuko Craft, Jim Dietz, Phillipe Druillet, Donato Giancola, Ann Hanson, H. R. Giger, Daniel Greene, Ron Kleeman, Arantzazu Martinez, Syd Mead, Moebius, Paul Oxborough, Alex Ross, Anthony J. Ryder, Dolfi Stoki, William Stout, Dan Thompson, Julie Bell and Boris Vallejo, Scott Waddell, and Jamie Wyeth--Publisher description.